2013
DOI: 10.7897/2230-8407.04304
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cavity: A Mirror to Hiv Manifestations

Abstract: A multitude of oral lesions have been described in individuals infected with the human immunodeficiency virus. Human immunodeficiency virus infection is a major interest and concern to dentists and other health care workers because of the many varieties of oral lesions often associated with Human immunodeficiency virus infection. Individual's tested seropositive for Human immunodeficiency virus infections are more susceptible to occurrence of lesions in oral cavity. This review covers the clinical and therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Candida albicans was the commonest (53%, n=9). Oral Candidiasis is a very common observation in HIV/AIDS patients in many studies reported in the literature [30,31]. It is an early manifestation of HIV that can occur in patients who appear otherwise healthy.…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans was the commonest (53%, n=9). Oral Candidiasis is a very common observation in HIV/AIDS patients in many studies reported in the literature [30,31]. It is an early manifestation of HIV that can occur in patients who appear otherwise healthy.…”
Section: Discussionmentioning
confidence: 99%